Fear, Stress, Susceptibility, and Problematic Social Media Use Explain Motivation for COVID-19 Preventive Behaviors Among Patients With Stroke and Their Caregivers - Shikha Kukreti PhD; Meng-Tsang Hsieh MD; Chieh-hsiu Liu MD, PhD; Jung-Sheng Chen PhD; Yi-Jung Chen MSc; Ming-Ta Hsieh MD; Chung-Ying Lin PhD; Mark D. Griffiths PhD (SAGE Publishing, 2024)
The COVID-19 pandemic presented significant challenges for individuals who experienced stroke and their caregivers. It is essential to understand the factors affecting preventive behavior in these populations. Therefore, the present study examined the factors that influenced COVID-19 preventive behavior and motivation for COVID-19 vaccine uptake among patients with stroke and their caregivers. A cross-sectional study comprising 191 participants (81 patients with stroke and 110 caregivers) was carried out. Participants completed a survey assessing fear of COVID-19, stress, perceived susceptibility, problematic social media use, preventive behaviors, and motivation for vaccine uptake. Statistical analyses included descriptive statistics, Pearson correlations, and multiple linear regressions. Motivation for COVID-19 vaccine uptake was significantly positively correlated with problematic social media use (r = 0.225, P  = .002), perceived susceptibility (r = 0.197, P  = .008), and fear of COVID-19 (r = 0.179, P  = .015), but negatively correlated with stress (r = −0.189, P  = .010). Caregivers, compared to patients, showed a lower level of preventive behavior (standardized coefficient = −0.23, P  = .017). Furthermore, higher levels of fear were associated with increased preventive behavior (standardized coefficient = 0.22, P  = .006), while greater stress correlated with lower preventive behavior (standardized coefficient = −0.38, P  < .001). Among patients with stroke and their caregivers, motivation of COVID-19 vaccine uptake and preventive behaviors were influenced by factors such as fear, perceived susceptibility, social media use, and stress. By using strategies such as targeted education, support, and communication campaigns, healthcare providers and policymakers may be able to enhance the well-being of patients with stroke and their caregivers during future pandemics.